A Comparison and Evaluation of the TOEIC and DET Writing Test - Yiran Hou (Journal of Linguistics and Communication Studies, 2024)
This essay aims to compare and evaluate the writing test of two widely used English language proficiency tests: the Test of English for International Communication (TOEIC) and the Duolingo English Test (DET). Bachman and Palmer’s (2010) assessment use argument (AUA) is used as a framework in this essay to compare and evaluate these two tests from three aspects: test score and reliability, validity and score interpretations, and consequences. The results show that some features of the TOEIC and DET writing tests (e.g., the DET writing test’s well-designed algorithm and lack of discourse level texts, the TOEIC writing test’s all direct tasks and DIF analysis used) make the two tests have some strengths and weaknesses respectively in each aspect.